Sri Lanka in 2022 and 2023: things fall apart—can Sri Lanka hold on? - Kelegama, T (University of California Press, 2024)

(untitled)
In the span of two years, Sri Lanka saw one of the biggest protests in South Asia, ousted a president and his government, defaulted on its sovereign debt, declared bankruptcy, appointed an unelected president, went to the IMF for a bailout loan, delayed elections, moved even further away from justice and reconciliation, and celebrated 75 years of independence. While the resignation of president Gotabaya Rajapaksa and his family from government hinted at change for the country, the appointment of Ranil Wickremesinghe demonstrated a firm commitment to lack of reform or accountability. Austerity, intimidation, instability, and further decay followed. These economic and non-economic shocks converged to reveal a country where multiple crises of dissent, debt, decay, and decline were inextricably bound together, with no way forward yet in sight.